The survival of civilization : depends upon our solving three problems--carbon dioxide, investment money, and population - Hamaker, John D. (Michigan : Hamaker-Weaver Publishing, 1982)
The book presents the profound synthesis of thought and principle that has emerged from John Hamaker's studies, and is found to be supported by advanced research proceeding from all the scientific disciplines he draws upon- from soil microbiology to nutritional science, glacial geology to palynology, pedalogy to paleoclimatology, etc.
Chapter 1. Our 100 percent junk food supply is destroying us -- Chapter 2. Food, energy and survival -- Chapter 3. Worldwide starvation by 1990 -- Chapter 4. The role of CO2 in the process of glaciation -- Chapter 5. The subsoil drainage system -- Chapter 6. The glacial process -- Chapter 7. Taxes, freedom and the costitution.
Includes bibliographical references.
Keywords: RENEWABLE ENERGY SOURCES